2017
DOI: 10.1787/9789282108130-4-en
|View full text |Cite
|
Sign up to set email alerts
|

Renegotiations in public-private partnerships: Theory and evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Many countries still lack adequate frameworks for effective public-private partnerships, which can improve the effectiveness of public investment (Engel et al, 2011). Capital market reforms can help channel domestic savings towards private investment (EBRD, 2015).…”
Section: Which Policies Can Help Address Investment Needs In the Eca mentioning
confidence: 99%
See 1 more Smart Citation
“…Many countries still lack adequate frameworks for effective public-private partnerships, which can improve the effectiveness of public investment (Engel et al, 2011). Capital market reforms can help channel domestic savings towards private investment (EBRD, 2015).…”
Section: Which Policies Can Help Address Investment Needs In the Eca mentioning
confidence: 99%
“… Several countries have begun to develop public-private partnership frameworks (Chile, Colombia, Peru). If designed well, these can improve the efficiency of public investment spending (Engel et al, 2011). Vashakmadze E, et al  LAC economies rank low on ease of business startup and tax compliance (South America and Central America), as well as trading across borders and registering property (Caribbean and South America) (World Bank, 2017b).…”
Section: Which Policies Can Help Address Investment Needs In the Lac mentioning
confidence: 99%
“…Ho (2006) contends that the fact that the government may bail out a distressed project and renegotiate with the developer in PPP projects can lead to serious opportunism problems in project administration. Engel et al (2014) posit that governments should limit contract renegotiations because they can erase the efficiency gains associated with PPPs. Hasselgren et al (2014) point out that sometimes objective reasons arise that make renegotiation necessary, even in contracts that initially seemed to consider all possible contingencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various solutions were tried and, in 1997, the government announced a restructuring plan under which it offered to take over the private concessions, assuming all their debt and all their liabilities to third parties (Bloomgarden and Blumenfeld, 2013). Evidence from Chile, Peru, and Colombia has shown that renegotiation of contracts can be substantial, and may end up in higher spending for the government and lower value-for-money when done outside of a competitive tender process (Engel et al, 2014).…”
Section: Physical Infrastructure Quality Of Infrastructure Hybrid Indmentioning
confidence: 99%
“…Bitran et al (2013) and Engel et al (2014) studied the renegotiation of contracts in these countries, in a theoretical and empirical setting, focusing mostly on PPPs in the area of transport infrastructure. The incidence of renegotiations in transport has been close to 80% of all contracts during 1980−2000, and this has increased more recently, but has also decreased in countries that have strengthened their PPP frameworks (Guasch et al, 2004).…”
mentioning
confidence: 99%